Different Competitive Growth Model for Finite Size Scaling Study of Rough Surfaces: A Smart Approach for Estimating Hydrophobicity - Banerjee, Diptonil; Mitra, S (International Journal of Computer Sciences and Engineering, 2015)
Rough surface has been produced by simulation in 1+1 dimension following different competitive growth models namely random deposition with ballistic deposition and random deposition with surface relaxation with ballistic deposition and calculated the corresponding scaling exponent. It is seen that though the nature of the interface evolution follows the well-established Edwards-Wilkinson growth model or Kardar–Parisi–Zhang model but the values of corresponding scaling exponents do not match exactly with the existing literature. Further it has been seen that the system does not switch over from growth region to saturation region suddenly after a single critical time as has been suggested by the existing theories but there are two distinct crossover regions where the system shows different scaling property. This theoretical finding has been coupled with existing Cassie-Baxter equation to relate the evolved roughness with hydrophobic response of the surface. In this regard, quantitative expression of the water contact angle based on simple assumptions has been represented.